Antimicrobial-Resistant Escherichia coli Survived in Dust Samples for More than 20 Years - Schulz, Jochen; Ruddat, Inga; Hartung, Jörg; Hamscher, Gerd; Kemper, Nicole; Ewers, Christa (Frontiers in Microbiology, 2016)
In a retrospective study, 119 sedimentation dust samples stored between five and 35 years from various barns of intensive livestock farming were evaluated for the occurrence of cultivatable Escherichia coli. Growth of E. coli occurred in 54 samples. Successful cultivation was achieved in samples from as early as 1994. The frequency of detection increased from earlier to later time periods, but the concentrations, which ranged between 3.4 × 102 and 1.1 × 105 colony-forming units per gram, did not correlate with sample age (Spearman rank correlation;, p > 0.05). We hypothesize that E. coli cells survived in dust samples without cell division because of the storage conditions. Dry material (dust) with low water activities (arithmetic mean < 0.6) and storage at 4°C in the dark likely facilitated long-term survival. Escherichia coli were isolated on MacConkey agar with and without ciprofloxacin supplementation. For 110 isolates (79 from non-supplemented media and 31 from supplemented media), we determined the E. coli phylotype and antimicrobial resistance. Six phylogenetic groups were identified. Phylo-groups A and B1 predominated. Compared to group A, phylogroup B1 was significantly associated with growth on ciprofloxacin- supplemented media (chi-square test, p = 0.003). Furthermore, the antibiotic resistance profiles determined by a microdilution method revealed that isolates were phenotypically resistant to at least one antimicrobial substance and that more than 50% were resistant to a minimum of five out of 10 antibiotics tested. A linear mixed model was used to identify factors associated with the number of phenotypic resistances of individual isolates. Younger isolates and isolates from fattening poultry barns tended to be resistant to significantly more antibiotics than older isolates and those from laying-hen houses (p = 0.01 and p = 0.02, respectively). Sample origin and storage conditions may have influenced the number of antimicrobial resistances. Overall, we found that under particular conditions, dust from farm animal houses can be reservoirs for antimicrobial-resistant E. coli for at least 20 years. The survival strategies that allow E. coli to survive such long periods in environmental samples are not fully understood and could be an interesting research topic for future studies.